إسهامات الإلنزام بأبعاد المسؤولية الاجتماعية في تحقيق الأداء الاقتصادي -دراسة حالة مؤسسة إتصالات الجزائر بولاية الوادي- - نسيب, أحمد (جامعة الوادي - University of Eloued, 2022)
This study aims to know the contributions of commitment to the dimensions of social responsibility in achieving economic performance in Algeria Telecom in El-Oued State, where we relied on the questionnaire as a tool for collecting data and information, from the study sample consisting of managers of the institution, so we retrieved (48) valid forms for analysis through the statistical program (SPSS). After the statistical treatment, the study reached several results, the most important of which is the acceptance of the main hypothesis that states that the commitment to social responsibility contributes to achieving economic performance in Algeria Telecom, which confirms the presence of a strong influence of the independent variable (dimensions of social responsibility) on the dependent variable (economic performance)
Contributions of adhering to the dimensions of social responsibility in achieving economic performance A case study of the Algeria Telecom Corporation in El-Oued Province-
مقال
Keywords: المسؤولية الاجتماعية ; الأداء الاقتصادي ; إتصالات الجزائر